2011
DOI: 10.1002/ijc.25988
|View full text |Cite
|
Sign up to set email alerts
|

Selective and efficient retardation of cancers expressing cytoskeleton‐associated protein 2 by targeted RNA replacement

Abstract: Human cytoskeleton-associated protein 2 (hCKAP2) is upregulated and highly expressed in various human malignances. hCKAP2 has microtubule-stabilizing characteristics and potentially regulates the dynamics and assembly of the mitotic spindle and chromosome segregation, indicating that hCKAP2 plays important functions during mitosis. In this study, we evaluated hCKAP2 as a plausible anticancer target through development and validation of a targeted cancer gene therapy strategy based on targeting and replacement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Moreover, a trans-splicing ribozyme that could selectively induce anti-viral activity in viral infected cells through the specific replacement of hepatitis C virus RNA has also been reported . Recently, we reported that the ribozyme selectively induced therapeutic genes in target RNA-expressing tumors both in cells and in vivo, thus effectively regressing the tumors, via RNA replacement through the trans-splicing reaction of cancer-specific RNA transcripts such as human telomerase reverse transcriptase (hTERT) Song et al, 2009), carcinoembryonic antigen (Jung and Lee, 2006), alpha-fetoprotein (Won and Lee, 2007), human cytoskeleton-associated protein 2 (Ban et al, 2011), and AIMP2-DX2 RNA (Won and Lee, 2012). In this study, a hypoxia-inducible trans-splicing ribozyme was developed, targeting the hTERT to overcome the therapeutic resistance observed in hypoxic tumors (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a trans-splicing ribozyme that could selectively induce anti-viral activity in viral infected cells through the specific replacement of hepatitis C virus RNA has also been reported . Recently, we reported that the ribozyme selectively induced therapeutic genes in target RNA-expressing tumors both in cells and in vivo, thus effectively regressing the tumors, via RNA replacement through the trans-splicing reaction of cancer-specific RNA transcripts such as human telomerase reverse transcriptase (hTERT) Song et al, 2009), carcinoembryonic antigen (Jung and Lee, 2006), alpha-fetoprotein (Won and Lee, 2007), human cytoskeleton-associated protein 2 (Ban et al, 2011), and AIMP2-DX2 RNA (Won and Lee, 2012). In this study, a hypoxia-inducible trans-splicing ribozyme was developed, targeting the hTERT to overcome the therapeutic resistance observed in hypoxic tumors (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, single gene repair would not be sufficiently effective. To overcome this limitation, our group and others developed trans ‐splicing ribozymes to reprogram viral transcripts (Carter et al, ; Carter, Keith, Barde, Fraser, & Fraser, ; Ryu et al, ; Ryu & Lee, ) or tumor‐related genes (Ban et al, ; Hong et al, ; Jeong et al, ; Jung & Lee, ; Kim et al, ; Kim et al, ; Kwon et al, ; Song et al, ; Won & Lee, ; Won & Lee, ; Won & Lee, ) and induce cell death, thus clearing virus‐infected or cancer cells (Figure ). This reprogramming leads to therapeutic gene expression only in virus‐infected or cancer cells, as long as the substrate is expressed only in diseased cells (such as in virally infected cells), and the ribozyme displays no off‐target effects such as splicing on unrelated cellular RNAs.…”
Section: Group I Intron Ribozymes As Therapeuticsmentioning
confidence: 99%
“…Won and Lee () developed an adenoviral hTERT‐targeting trans ‐splicing ribozyme in which the 3′‐exon had been exchanged with E1A, thus potentially converting a replication‐incompetent adenoviral vector to replication‐competent virus in hTERT‐expressing cells via a precise trans ‐splicing reaction. Trans ‐splicing ribozymes specific for carcinoembryonic antigen (CEA; Jung & Lee, ), cytoskeleton‐associated protein 2 (CKAP2; Ban et al, ; Kim et al, ), alpha‐fetoprotein (AFP; Won & Lee, ), and pancreatic adenocarcinoma upregulated factor (PAUF) RNA (Kim et al, ), all of which are over‐expressed in various cancers, have also been developed, and the abilities of these constructs to induce therapeutic transgene expression through target RNA reprograming have been specifically validated in target RNA‐expressing cells.…”
Section: Group I Intron Ribozymes As Therapeuticsmentioning
confidence: 99%
“…[26][27][28][29][30][31] Moreover, we designed ribozymes that can specifically transfer the therapeutic gene into target RNA-expressing cancer cells, resulting in effective retardation of tumors in vivo through RNA replacement by a trans-splicing reaction with cancer-specific RNA, such as human telomerase reverse transcriptase RNA or human cytoskeleton-associated protein 2 RNA. [32][33][34][35][36] In this study, we developed trans-splicing ribozymes that can specifically target the KRAS G12V transcript as a new targeting agent specifically against cancers harboring KRAS mutation. The ribozyme was designed to selectively splice and reprogram KRAS G12V transcripts, but not wild-type KRAS, inducing the therapeutic transgene specifically in cancer cells harboring the KRAS G12V mutation both in cells and in vivo.…”
Section: Introductionmentioning
confidence: 99%